Conversation CONVERSATION STYLE: ANALYZING TALK AMONG ‘’KICK ANDY'S TALK SHOW WITH THE FIVE TOWER STATE NOVEL'S AUTHOR’’ Abstrack The conversation analysis contained in the Talk Show Kick Andy video contains four topics, including the topic of conversation, the str - Nurus silvia Silvi; Yuliyanto Sabat (STKIP PGRI SIDOARJO, 2022)
Abstrack The conversation analysis contained in the Talk Show Kick Andy video contains four topics, including the topic of conversation, the structure of the conversation, the transfer of conversation, and the coherence of conversational discourse. On the topic of conversation, three topics were found, namely general topics, ongoing topics and real topics. Furthermore, in the conversation structure, the topic of conversation is found at the beginning of the conversation, the core of the conversation, and the end of the conversation. The conversational speech transfer contains two types of conversational speech transfer. The first is speech switching with an arranged turn, the second is a speech transfer with an automatic turn. The last conversation analysis is the coherence of conversational discourse. Cohesion is shown in the cohesion and coherence in the content of the conversation. Keywords: conversation analysis, topic of conversation, change the conversation.